Společenstva vodních měkkýšů řeky Oravy - Luboš Beran; Erika Šlachtová; Viktorie Klobušická; Jaroslav Beran (Malacologica Bohemoslovaca)
We analyse the diversity of aquatic molluscs of the river Orava in north-western Slovakia. The river Orava has been part of the protected area “Rieka Orava” since 1997 and included in NATURA 2000 as a Site of Community Importance since 2004. Although the malacofauna of the Orava reservoir had previously been partially investigated, the river itself had not yet been studied in detail. A total of 17 species of aquatic molluscs were found at 11 sites along the river, including 7 species of gastropods and 10 species of bivalves. Notable finds include the discovery of the rare Odhneripisidium tenuilineatum and large populations of Unio crassus s. lato (U. crassus sensu stricto and/or U. nanus), the species of European importance. The presence of these species emphasises the ecological integrity of this ecosystems and justifies its protection.